STRUCTURAL SYNTHESIS OF BAR SYSTEMS BASED STABILITY OF EQUILIBRIUM - and (Municipal economy of cities. Series: «Economy science», 2013)
Pivotal systems design is conducted in the basis of Castigliano functional stationary state with complementary conditions. Virtual state with reduced internal forces is for compressed pivots introduced.